Tailoring the Pore Surface of 3D Covalent Organic Frameworks via Post‐Synthetic Click Chemistry. (29th November 2021) - Gui, Bo; Liu, Xuefen; Cheng, Yuanpeng; Zhang, Ya; Chen, Pohua; He, Minghui; Sun, Junliang; Wang, Cheng
Abstract: Three‐dimensional covalent organic frameworks (3D COFs) have gained increasing attention for their attractive features. However, the development of 3D COFs is strongly restricted, mainly due to their synthetic difficulty and complicated structure determination. Post‐synthetic modification, which can avoid these problems by incorporating functional moieties into a predetermined framework, provides an alternative way to construct 3D COFs with specific functions. Herein, we report the designed synthesis and characterization of a series of highly crystalline 3D COFs with different loadings of ethynyl groups. Notably, these alkyne‐tagged 3D COFs provide a platform for targeted anchoring various specific groups onto the pore walls via click reactions. Moreover, the pore surface engineering can accordingly change their properties, for example, the obtained click products exhibited higher CO2 /N2 selectivity. We describe a simple but powerful strategy to build functional 3D COFs, which will certainly advance them for a ranging of interesting applications in the future. Abstract : A series of highly crystalline 3D COFs with variable loadings of ethynyl groups were designed and synthesized. Remarkably, these alkyne‐tagged 3D COFs provide a platform for targeted anchoring various organic groups onto the pore walls via click reactions, which can accordingly change their properties, e.g., the obtained click products exhibited higher CO2 /N2 selectivity.